2004
DOI: 10.1074/jbc.m405100200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate-1/SHP-2 Interaction, a Phenotype-dependent Switching Machinery of Insulin-like Growth Factor-I Signaling in Vascular Smooth Muscle Cells

Abstract: Insulin-like growth factor-I (IGF-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 46 publications
4
55
0
1
Order By: Relevance
“…However, Hayashi and colleagues showed that PI-3 kinase phosphorylation may lead to either Akt or ERK activation depending on the docking proteins associated with IGF-1 receptor. These investigators postulated that such ''bifurcated'' response may underline different IGF-1 response between primary VSMCs and those from passages 2-5 [47]. The increased basal ROS and phosphorylated ERK (possibly as a result of increased ROS) in late passage VSMCs, observed in our study may possibly represent a point of saturation when the cells are no longer responsive to IGF-1.…”
Section: Discussionmentioning
confidence: 52%
“…However, Hayashi and colleagues showed that PI-3 kinase phosphorylation may lead to either Akt or ERK activation depending on the docking proteins associated with IGF-1 receptor. These investigators postulated that such ''bifurcated'' response may underline different IGF-1 response between primary VSMCs and those from passages 2-5 [47]. The increased basal ROS and phosphorylated ERK (possibly as a result of increased ROS) in late passage VSMCs, observed in our study may possibly represent a point of saturation when the cells are no longer responsive to IGF-1.…”
Section: Discussionmentioning
confidence: 52%
“…42 In addition, IGF-I appears to have differential effects on SMC proliferation and differentiation, which depend on SMC phenotype. 43 Spindle-shaped SMCs require IGF-I signalling for maintenance of the contractile phenotype, whereas epithelioid SMCs increase migration and proliferation upon IGF-I treatment. Thus, besides RA, TNF-α, angiotensin II and IGF-I also contribute to SMC diversity.…”
Section: Biochemical Factorsmentioning
confidence: 99%
“…Hayashi and colleagues [40][41][42] developed a chemically defined culture system for aortic VSMC containing insulin-like growth factor I (IGF-I) and laminin substratum that they proposed maintains the differentiated phenotype of VSMC as judged by semiquantitative reverse transcriptase (RT)-PCR of marker genes. These authors proposed that changes in the balance between the phosphatidyl inositol 3 kinase (PI3K)/Akt pathway and the extracellular signal-regulated mitogen-activated kinase 1/2 (ERK1/2 MAPK) pathway determine the phenotype of VSMC in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…When VSMC are dissociated, they become deprived of the mechanical stimuli, which have been proved by numerous studies [12][13][14][15][16][17][18][19][20][21] to play a role in PM. Second, if inhibition of ERK and the p38 MAPK pathways is a prerequisite for maintaining the differentiated phenotype [40][41][42][43], how can one explain the findings that stretch not only increased ERK and p38 MAPK activity [44][45][46], but also at the same time was sufficient for maintaining the differentiated phenotype [16,17]?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation